THEORETICAL STUDY AND CHARACTERISTICS OF YARNS IN THE PRODUCTION OF CIRCULAR KNIT FABRICS - Soliyev, Azizbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article analyzes the properties of yarns used in circular knit fabrics, which are currently in high demand, as well as the research conducted by scientists in this field. Based on these analyses, conclusions were drawn regarding the investigation of the deformational properties of yarns for the production of circular knit fabrics and the mathematical modeling of yarn as a solid body.